Spectrophotometric Determination of Desloratadine in Bulk and Tablet Forms - M. Patel, Jitendra; Talele, G.S.; Fursule, R.A. (Asian Journal of Chemistry, 2016)
A new simple and sensitive spectrophotometric method in UV has been developed for the quantitative estimation of desloratadine in bulk and dosage forms. Desloratadine shows maximum absorbance at 282.5 nm. Beers law was obeyed in concentration range of 16–24 mcg/mL. The developed method was validated statistically and by recovery studies. The recovery study was found to be between 97 to 101%.